Case Report: Effective extracorporeal cardiopulmonary resuscitationin prolonged cardiac arrest - Yan, Wangjun; Tang, Guanxiu; Wang, Hui; Li, Houshen; Liang, Luobin; Li, Yijiang; Zhao, Shangping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiac arrest is a major cause of mortality, and outcomes after prolonged conventional cardiopulmonary resuscitation (CCPR) are often poor. Extracorporeal cardiopulmonary resuscitation (ECPR), involving veno-arterial extracorporeal membrane oxygenation (VA-ECMO), offers a rescue strategy for refractory cardiac arrest by providing cardiopulmonary support to allow treatment of underlying causes. This case report illustrates the potential of ECPR in an unusually prolonged cardiac arrest.Case descriptionWe report a case of a 44-year-old man who experienced sudden prolonged cardiac arrest secondary to acute myocardial infarction and was successfully rescued with ECPR and VA-ECMO. The patient presented with 8 h of chest pain and went into ventricular fibrillation (VF) out of hospital; despite aggressive CCPR for approximately 155 min, return of spontaneous circulation was not achieved until ECPR was initiated. At 12:17 on the day of presentation, VA-ECMO was initiated in the emergency department after continuous CCPR. Subsequent coronary angiography revealed severe multivessel disease with critical proximal left anterior descending (LAD) artery stenosis, which was successfully treated with percutaneous coronary intervention (PCI) while the patient remained on ECMO support. The patient's post-arrest care included mechanical ventilation, targeted temperature management, inotropic and vasopressor support, antithrombotic therapy and aggressive neuroprotective measures. A large infarct in the left occipitotemporal lobe was identified on CT, but intensive care with hypothermia and sedation allowed the patient to survive with intact neurological function. ECMO was weaned off on day 9 of admission, and the patient was extubated on day 12. He subsequently made a full neurological recovery and was transferred out of the intensive care unit in stable condition.ConclusionThis case illustrates that even extremely prolonged cardiac arrest can result in good outcomes when managed promptly with ECPR and comprehensive critical care. It highlights the potential of ECPR to improve survival and neurological outcomes after refractory cardiac arrest and underscores the importance of rapid ECMO deployment in selected patients.